First description of supernumerary chromosomes in Ictalurus punctatus Rafinesque 1818 reveals active ribosomal genes in the B complement - Do Prado, Fernanda Dotti [UNESP]; Daniel, Sandro Natal [UNESP]; Penitente, Manolo [UNESP]; Hashimoto, Diogo Teruo [UNESP]; Foresti, Fausto [UNESP]; Porto-Foresti, Fábio [UNESP] (Institute of Systematics and Evolution of Animals, Polish Academy of Sciences, 2016)
The North American channel catfish Ictalurus punctatus Rafinesque 1818 is cultivated in the United States, Asia and Brazilian fish farms, and also utilized as a model species in aquaculture and genetic studies. In this work, cytogenetic analysis of I. punctatus from Brazilian aquaculture revealed for the first time the presence of extra elements (supernumerary or B chromosomes) in this species. These elements were characterized as dot-like micro B chromosomes and were found in three individuals (varying from 0 to 1) and in one individual with higher incidence per cell (varying from 0 to 5; mean number of Bs per cell = 2.01). More specific cytogenetic techniques in this individual revealed 58 A chromosomes (standard complement) containing heterochromatic bands in the centromeric regions, a single Ag-NOR in a subtelocentric pair (also positive for 18S rDNA using the FISH technique) and multiple 5S rDNA clusters in three different subtelocentric chromosomes. Four B chromosomes were entirely Ag-NOR positive (also fully heterochromatic) and three presented 18S rDNA clusters by FISH. The occurrence of Ag-NOR and 18S ribosomal genes in bothAand B chromosome complements may indicate an intraspecific origin for these extra chromosomes. Additionally, the terminal location of 18S ribosomal clusters in the Ag-NOR-bearing chromosomes and the presence of active NOR in the B chromosomes suggested that breakage events may be related to a possible recent origin of these extra elements. We suggest this data may be useful as cytogenetic information for future elucidation of the composition, origin and evolution of extra chromosomes in fishes.
Keywords: Ag-NOR; B chromosomes; Channel catfish; Constitutive heterochromatin; Cytogenetics